Representasi (Eksternal-Internal) pada Penyelesaian Masalah Matematika - Achmad Faruq; Ipung Yuwono; Tjang Daniel Chandra (JRPM (Jurnal Review Pembelajaran Matematika), 2016)
This study aimed to describe the pictorial and schematic representations of student understanding. The subjects were 31 students of grade VIII. The results of this study is two pictorial representations (right and wrong) and two schematic representation (right and wrong). Representation understanding of student described as follows: translational stage, students read the word problem to identify relational statements and quantity, then he transforms the mathematical idea into another form that is more easily understood. Integration stage, students identifying relational relationships between mathematical ideas to be organized into a scheme or image. Solution stage, students devise a solution based on the scheme or image that was created, and then perform calculations and check the answer.